2008
DOI: 10.1086/590948
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Accretion History of Terrestrial Planets from Runaway Growth through to Late Time: Implications for Orbital Eccentricity

Abstract: Remnant planetesimals might have played an important role in reducing the orbital eccentricities of the terrestrial planets after their formation via giant impacts. However, the population and the size distribution of remnant planetesimals during and after the giant impact stage are unknown, because simulations of planetary accretion in the runaway growth and giant impact stages have been conducted independently. Here we report results of direct N-body simulations of the formation of terrestrial planets beginn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 50 publications
5
74
0
Order By: Relevance
“…However, the radial concentration of planetary mass seen in our own solar system can be replicated if terrestrial planet formation begins from a narrow annulus ( Figure 3) (Morishima et al 2008;Hansen 2009). We mimic this in our last ensemble, "annulus" (ANN).…”
Section: Methodsmentioning
confidence: 74%
“…However, the radial concentration of planetary mass seen in our own solar system can be replicated if terrestrial planet formation begins from a narrow annulus ( Figure 3) (Morishima et al 2008;Hansen 2009). We mimic this in our last ensemble, "annulus" (ANN).…”
Section: Methodsmentioning
confidence: 74%
“…The terrestrial planets have low eccentricities and inclinations, Earth and Venus both have e < 0.02 and i < 3 • , properties which has proved difficult to match in accretion simulations. O'Brien et al (2006) and Morishima et al (2008) reproduced low eccentricities and inclinations largely due to remaining planetesimals which damp the orbital excitation of the planets. A metric used as a diagnostic of the degree of success of the simulations in reproducing the dynamical excitation of the terrestrial planets is the angular momentum deficit (AMD; Laskar 1997):…”
Section: The Planetsmentioning
confidence: 97%
“…The radial mass concentration of the solar system's terrestrial planets is S c = 89.9, which indicates high radial mass concentration because the masses of Mercury and Mars are small and the orbital distance between Venus and the Earth is also relatively small. Previous studies have shown that it is difficult to reproduce such a high mass concentration (e.g., Raymond et al 2009;Morishima et al 2010); a way to account for this statistic in N-body simulations is to assume a mass distribution initially confined to a narrow annulus (Morishima et al 2008;Hansen 2009), or in other words to assume an initially large S c . In the grand tack model (e.g., Walsh et al 2011;, Jupiter sweeps up to ∼1.5 AU and embryos are eventually confined to a relatively compact region.…”
Section: Origin Of the Solar System's Terrestrial Planetsmentioning
confidence: 99%